Socioeconomic Factors, Food Supply and Food Security among Communities at the Malaysia-Thailand Border: A Human Security Approach - Bakri Mat; Ku Nurasyiqin Ku Amir (International Journal of Supply Chain Management, 2019)
Food security is one of the non-traditional security components that forms the basic needs of a nation, households, and individuals. Any problem in food supply or disruption in any of the four key elements of food security will threaten security and well-being of the citizens. In Malaysia, although food availability is ensured through via local production and imports at national level, accessibility and utilization are not yet fulfilled as certain groups and households are still unable to access and utilise adequate food accordingly. Therefore, this research attempts to examine the socioeconomic factors that may contribute towards food insecurity among Malaysian households within communities in Malaysia-Thailand border using human security approach. This study is conducted using qualitative research method to collect and analyse both primary and secondary data. Primary data was obtained through official documents and an in-depth interview with key informants among Malaysian households of the communities near Malaysia-Thailand border, local leaders and academicians. Meanwhile, the secondary source of data was obtained from published materials and online documents such as books, journal articles and reports. The findings indicate that socioeconomic factors were pertinent in contributing towards food insecurity among the households in form of household income, insufficient assistance program, and high living costs. These factors form the main foundation in ensuring the sanctity and wellbeing of the households. In designing state policies, the socioeconomic issues should be prioritized as in ensuring human security of the vulnerable groups, specifically the B40 households. In addition, continuous effort in developing societal empowerment and resilience are vital to achieve citizen wellbeing.